Pembuatan Sign System Sebagai Penanda Batas Antardusun di Desa Sambirejo, Kabupaten Jombang - Nabila Yasmin Widyana Damayanti; Yanda Bara Kusuma (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2023)
Installing a sign system as a boundary marker between hamlets is one of the development efforts undertaken to improve the existing infrastructure in Sambirejo Village. It aims to direct visitors and provide information about the areas they enter, where each hamlet has its own tours and even MSME. The method of implementing the community service activity program carried out in the KKN-T MBKM UPN "Veteran" East Java activities is to use a qualitative descriptive approach because it describes the phenomena that occur in depth, and describes the responses without testing the hypothesis. This activity starts from conducting a field survey by looking for a location where the sign system will be installed. Followed by the planning and design, manufacture, and installation of sign systems. The government is expected to continue its commitment to improve infrastructure development, as having reliable infrastructure is essential to support infrastructure development and business growth.